Pengaruh Esktrak Daun Krokot (Portulaca oleracea) Terhadap Kadar Malonialdehide (MDA) Pada Tikus Yang Diinduksi Aloksan - Sukma Sahreni; Isramilda Isramilda; Rezha Irshadi Ashari (Pusat riset dan Inovasi Nasional, 2023)
Background: Diabetes mellitus is a degenerative disease caused by the pancreas being damaged in production or insulin cannot work effectively. Portulaca Oleracea Leaf Extract can help reduce levels of Malondialdehyde. The purpose of this study was to analyze the effect of Portulaca Oleracea leaf extract on malondialdehyde levels in alloxan-induced rats as a diabetes model.Methods: There were 30 rats in this study divided into 5 groups, each group consisting of 6 rats. The negative control group was only given aquadest and standard rat feed, the positive group was induced with alloxan, the treatment group 1 was induced with alloxan and Portulaca Oleracea leaf extract at a dose 60 mg/200grBW, treatment group 2 was induced with alloxan and Portulaca Oleracea leaf extract at a dose 90 mg/200grBW and treatment group 3 was induced by alloxan and Portulaca Oleracea leaf extract at a dose 110 mg/200grBW rats. Analysis of the results used the One Way Anova test followed by Post Hoc LSD analysis to see differences between groups.Results: The results of One Way Anova test on Malondialdehyde levels showed that there was an effect after intervention of Portulaca Oleracea leaf extract among the five treatment groups p = 0.000. The results of Post Hoc LSD test showed that Portulaca Oleracea leaf extract had effective inhibits the formation of malondialdehyde activity at a dose of 90 mg/200grBB p = 0.145.Conclusion: It can be concluded that Portulaca Oleracea leaf extract can reduce Malondialdehyde levels.